2016
DOI: 10.1080/01639625.2016.1237829
|View full text |Cite
|
Sign up to set email alerts
|

“I Wanted to Feel the Way They Did”: Mimesis as a Situational Dynamic of Peer Mentoring by Ex-Offenders

Abstract: Despite growing enthusiasm for peer mentoring as a criminal justice intervention, very little is known about what actually happens within these relationships. Drawing upon an ethnographic study of peer mentoring in the North of England this article will foreground the concept of 'inspiration' in these settings. It will argue that Rene Girard's theory of mimesis offers a framework with which to analyse role modelling in mentoring relationships and that a Girardian reading also offers interesting insights into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 21 publications
(13 reference statements)
1
46
0
Order By: Relevance
“…Based on “the concept of non-professionals providing social, emotional, and/or instrumental support to others with whom they share the same values, experiences, and lifestyle” (Einat, 2017, p. 205; see also Roberts & Rappaport, 1989), it makes sense that peer mentoring is also supposed to benefit mentees who learn from their mentors. For example, Buck’s (2017) ethnographic study using 44 interviews showed that peer mentors can inspire mentees because mentees admire their mentors and thus imitate their mentors’ desire for self-improvement. The imitation, however, should be accompanied by individual mentee’s will to change (i.e., human agency), which is positively influenced by the presence of role models.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on “the concept of non-professionals providing social, emotional, and/or instrumental support to others with whom they share the same values, experiences, and lifestyle” (Einat, 2017, p. 205; see also Roberts & Rappaport, 1989), it makes sense that peer mentoring is also supposed to benefit mentees who learn from their mentors. For example, Buck’s (2017) ethnographic study using 44 interviews showed that peer mentors can inspire mentees because mentees admire their mentors and thus imitate their mentors’ desire for self-improvement. The imitation, however, should be accompanied by individual mentee’s will to change (i.e., human agency), which is positively influenced by the presence of role models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Antisocial characteristics include risk factors for crime and deviance (e.g., legal cynicism and negative emotional state) and aggressiveness. For prosocial characteristics, we examine predictors of human agency (i.e., crystallization of discontent and a sense of meaning and purpose in life), which prior researchers studied as signs of offender reformation (Buck, 2017; Heidemann et al, 2016; LeBel et al, 2015). We also examine a concept rarely examined in criminology, virtue (e.g., humility and gratitude).…”
Section: The Present Studymentioning
confidence: 99%
“…Relapse by either can have negative ramifications for the recovery of the other. There is little empirical evidence regarding the benefits or negative impacts of mentoring on mentors' desistance from crime or substance use, either in the justice system generally or in VTCs specifically (see Buck, 2017;Dugdale, Elison, Davies, Ward, & Dalton, 2016). Preliminary information has indicated that mentoring enhances the recovery process for mentors themselves, primarily by allowing mentors to focus on the recovery of others and remaining engaged with resources that help maintain their own recovery (Dugdale et al, 2016).…”
Section: Mentors In Vtcsmentioning
confidence: 99%
“…More important than the desire inspired, is the mentee's opportunity to practice planning for possible future directions. The mentor's generative helping role can become the basis of a viable model for the mentee's future life plans (Buck, 2016).…”
Section: Hope and Generativitymentioning
confidence: 99%